Avances en el desarrollo de equipos para la colección y almacenamiento de energía solar distribuida - Ponce, S. (2016)
In the present work is raises them features of the model of absorber patented recently by the company that carries forward the construction of the prototype of collector solar cylinder-parabolic with storage in the line focal. The same, and after several modifications, was presented in the Office Spanish of Patents and Marks (OEPM) and it was accepted at the end of the year 2015. This model attempts to provide a principle of feasible solution to the problem of the manageability of the production of energy solar thermal, depending on the storage. Also is indicated the problems yet to be resolved with respect to the final configuration based on each of the combinations of thermal fluids and heat carrier fluid which could be used, depending on the temperature range that you want to achieve and the purpose of the equipment.